HUBUNGAN AKTIVITAS FISIK, SCREEN BASED ACTIVITY DAN SLEEP HYGIEN DENGAN KUALITAS TIDUR PADA REMAJA USIA 15-18 TAHUN (Studi pada Siswa di SMA Negeri 1 Ungaran) - Anisa Ayu Yolanda; M. Arie Wuryanto; Nissa Kusariana; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Sleep as basic human needs that must be fulfilled based on quality and quantity. Health problems related to sleep in a long period in adolescence will have an impact on health status in adulthood.The purpose of the study to analyze physical activies, screen based activity, and sleep hygiene to sleep quality in adolescent. Analytical research with cross sectional approach. research conducted in June to December 2017 in SMA Negeri 1 Ungaran with total sample 102 students, selected by multistages random sampling. Data collection was conducted through interviews used a questionnaire Adolescent Sleep Hygiene Scale (ASHS) and Pittsburgh Sleep Quality Index (PSQI). Respondents with low physical activities (63,7%), have bad habit of screen based activity (93,1%), bad sleep hygiene (54,9%) and bad sleep quality (76,5%). Based on analysis bivariat test Rank Spearman, there was relationship between sleep hygiene with sleep quality (p=0,003). Meanwhile, there was no relationship between physical activity (p=0,927) and screen based activity (p=0,216) with sleep quality.